2011
DOI: 10.1007/s11882-011-0200-0
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Immunomodulatory Factors in the Development of Immune Tolerance

Abstract: Emerging evidence suggests that exposures during pregnancy and the early postnatal period can modify gene expression and disease propensity. Diet is a major environmental exposure, and dietary factors, including polyunsaturated fatty acids, probiotics, oligosaccharides, antioxidants, folate, and other vitamins, have effects on immune function. Some also have been implicated in reduced risk of allergy in observational studies. Intervention trials with polyunsaturated fatty acids, probiotics, and oligosaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 86 publications
2
36
0
Order By: Relevance
“…Whether these mechanisms also account for prenatal allergen tolerance mechanisms is not completely clarified. However, emerging evidence suggests that exposures during pregnancy and the early postnatal period can modify gene expression and thus disease propensity (10). Thus, it could be shown that cord blood regulatory T cells are depressed in quantity (total numbers) and quality (function) in atopic as compared to nonatopic mothers (11,12).…”
Section: Tolerance Induction In the Prenatal/perinatal Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether these mechanisms also account for prenatal allergen tolerance mechanisms is not completely clarified. However, emerging evidence suggests that exposures during pregnancy and the early postnatal period can modify gene expression and thus disease propensity (10). Thus, it could be shown that cord blood regulatory T cells are depressed in quantity (total numbers) and quality (function) in atopic as compared to nonatopic mothers (11,12).…”
Section: Tolerance Induction In the Prenatal/perinatal Periodmentioning
confidence: 99%
“…In this respect, food allergen exposure in the prenatal/perinatal period has been implicated to rather induce tolerance than to trigger disease-causing reactions, such as allergic sensitization (10). Most of recent human studies have focused on peanut as allergen.…”
Section: Tolerance Induction In the Prenatal/perinatal Periodmentioning
confidence: 99%
“…Further studies should aim at optimizing infant feeding regimens. Supporting the most favorable "tolerogenic" microenvironment in the gut during the period of food allergen introduction is also likely to involve "optimal" colonization of the gastrointestinal tract, breastfeeding, and other dietary factors with immunomodulatory capacity [39,40] .…”
Section: Resultsmentioning
confidence: 99%
“…There are data to suggest that starting complementary foods before 3-4 months of age may increase the risk of allergic disease [37,38] . At that age, the gut is more permeable and gastrointestinal colonization is not yet well established, which might contribute to the observed risk increase [39,40] . Consequently, many international infant feeding guidelines for allergy prevention recommend introduction of any solid food after 4 months of age [32][33][34][35][36] .…”
Section: The "Optimal" Window Of Introduction Of Complementary Foods mentioning
confidence: 99%
“…Dietary components may also alter the epigenome to influence immune function, and there is a particular window of vulnerability for this during early development (West et al, 2011). Folate for example is a methyl donor.…”
Section: Perinatal Dietary Influence On Immune System Developmentmentioning
confidence: 99%